Exploring the potential of tomato juice (Solanum lycopersicum L.) patch for tooth bleaching - Laifa Annisa Hendarmin; Berliana Novianita; Yuni Anggraeni; Khairunissa Febriyanti (Journal of Dental Research, Dental Clinics, Dental Prospects)
Background. Tomato, renowned for its tooth-whitening properties due to its hydrogen peroxide and peroxidase enzyme content, requires formulation for enhanced applicability. This study assessed the dental whitening efficacy of a patch containing tomato juice as the active ingredient. Methods. Tomato juice patches were formulated at concentrations of 55%, 60%, and 65%. A control group (C) containing a 12% hydrogen peroxide patch was also included. A matrix layer of the patches was prepared using the solvent casting method at 40 for 18 h, with Tegaderm™ applied as the backing layer. For the dental whitening procedure, each group of patches was applied to the labial surface of anterior stained teeth (n=6/group) for 3 h, repeated 14 times. Tooth brightness was evaluated qualitatively and quantitatively using digital dental photo CIEL*a*b* analysis. Meanwhile, enamel surfaces were examined under a scanning electron microscope (SEM). Repeated-measures analysis of variance (ANOVA) was employed for statistical analysis. Results. The application of tomato juice patches led to enhanced tooth brightness. The patch containing 65% tomato juice significantly improved stained tooth brightness (P<0.05). SEM analysis revealed less enamel erosion with the 65% tomato juice patch compared to the 12% hydrogen peroxide patch. Conclusion. Tomato juice patches effectively increased tooth brightness while minimizing demineralization. Further research is needed to optimize formulation and explore its potential.